2024
DOI: 10.3390/drones8030088
|View full text |Cite
|
Sign up to set email alerts
|

Yield Prediction Using NDVI Values from GreenSeeker and MicaSense Cameras at Different Stages of Winter Wheat Phenology

Sándor Zsebő,
László Bede,
Gábor Kukorelli
et al.

Abstract: This work aims to compare and statistically analyze Normalized Difference Vegetation Index (NDVI) values provided by GreenSeeker handheld crop sensor measurements and calculate NDVI values derived from the MicaSense RedEdge-MX Dual Camera, to predict in-season winter wheat (Triticum aestivum L.) yield, improving a yield prediction model with cumulative growing degree days (CGDD) and days from sowing (DFS) data. The study area was located in Mosonmagyaróvár, Hungary. A small-scale field trial in winter wheat wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 71 publications
1
1
0
Order By: Relevance
“…The general average of the genotypes was found to be 0.64. These results are in concurrence with those ofLopes and Reynolds (2012) andZsebő et al (2024) who inferred that NDVI values remained effective in differentiating the wheat genotypes and could be preferred over destructive sampling techniques to sort out the most performing genotypes. Moreover,Swoish et al (2022),Guan et al (2019) andNaser et al (…”
supporting
confidence: 88%
See 1 more Smart Citation
“…The general average of the genotypes was found to be 0.64. These results are in concurrence with those ofLopes and Reynolds (2012) andZsebő et al (2024) who inferred that NDVI values remained effective in differentiating the wheat genotypes and could be preferred over destructive sampling techniques to sort out the most performing genotypes. Moreover,Swoish et al (2022),Guan et al (2019) andNaser et al (…”
supporting
confidence: 88%
“…However, these sampling techniques tend to be labor-intensive, tedious, expensive and time-consuming. Moreover, it has been reported that sampling errors lead to misleading results in detecting and differentiating crop genotypes (Elliot and Regan, 1993;Ma et al, 2001;Babar et al, 2006;Kiran et al, 2015;Marino and Alvino, 2019;Zsebő et al, 2024).…”
Section: Introductionmentioning
confidence: 99%